Gender dan Seksualitas Diaspora Masyarakat Asmat: Analisis Poskolonial - Evelin Giovani; Nurul Istiqomah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to explore the gender and sexuality values ​​of the Asmat diaspora who inhabit the Merauke Regency area using a postcolonial perspective, namely Subaltern Gayatri Charavorty Spivak. This research method uses a qualitative descriptive research technique with a phenomenological approach model, namely by conducting interviews and observations of informants. The results of this study are that women from the Asmat diaspora experienced a shift in customary values ​​after the entry of monotheistic religions into Papua, received less education about sexual rights, and experienced powerlessness because they did not have authority over their bodies and the opportunity to regulate their own lives. The conclusion of this study is that women in the Asmat diaspora in Merauke Regency experience epistemic violence due to the shift in customary values, limited access to sexual knowledge, economic powerlessness, and lack of power over their bodies which places them in a subaltern position.. Keywords: Asmat Women, Bodily Authority, Spivak, Subaltern.